(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
For a long period of time, the main regulator of relations associated with various encroachments on the bodies of the dead and the places of their burial was religion; however, the transition of society from traditional to post-industrial predetermined the changes in settlement of the analyzed crimes. In order to preserve the moral principles and moral health of society, the Criminal Code of the Russian Federation singles out an independent group of crimes that infringe on public morality, one of which is Desecration of the dead bodies and their burial places. The article discusses issues related to the commission of encroachments on the bodies of the dead and the places of their burial. They presented the description and characteristics of the objects of encroachment, as well as qualified compositions. The dialectical approach to the disclosure of legal phenomena and processes using general scientific (systemic, logical, analysis and synthesis) and specific scientific methods are utilized to gratify the aims of the study. The author substantiates the consistency of the approach regarding the synonymy of the concept "violation" and "desecration".